There is more to risk and safety planning than dramatic risks: Mental health nurses' risk assessment and safety‐management practice. (2nd December 2015) - Higgins, Agnes; Doyle, Louise; Downes, Carmel; Morrissey, Jean; Costello, Paul; Brennan, Michael; Nash, Michael
Abstract: Risk assessment and safety planning are considered a cornerstone of mental health practice, yet limited research exists into how mental health nurses conceptualize 'risk' and how they engage with risk assessment and safety planning. The aim of the present study was to explore mental health nurses' practices and confidence in risk assessment and safety planning. A self‐completed survey was administered to 381 mental health nurses in Ireland. The findings indicate that nurses focus on risk to self and risk to others, with the risk of suicide, self‐harm, substance abuse, and violence being most frequently assessed. Risk from others and 'iatrogenic' risk were less frequently considered. Overall, there was limited evidence of recovery‐oriented practice in relation to risk. The results demonstrate a lack of meaningful engagement with respect to collaborative safety planning, the identification and inclusion of protective factors, and the inclusion of positive risk‐taking opportunities. In addition, respondents report a lack of confidence working with positive risk taking and involving family/carers in the risk‐assessment and safety‐planning process. Gaps in knowledge about risk‐assessment and safety‐planning practice, which could be addressed through education, are identified, as are the implications of the findings for practice and research.